Peningkatan Keterampilan Menyimak Melalui Metode Bermain Bisik Berantai Siswa Kelas V SDI No 147 Palalakkang Kecamatan Galesong Kabupaten Takalar - Muh Fadli Anugrah M; Andi Syukri Syamsuri; M. Agus (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2023)
This research aims to describe the improvement of listening skills using the chain whisper playing method in class V students of SDI No. 147 Palalakkang, Galesong District, Takalar Regency. This type of research is Classroom Action Research (PTK). The research subjects were 10 people consisting of 5 male students and 5 female students. Data collection methods are carried out through observation and tests. This research instrument was carried out in two cycles. The results of the research after implementing the actions for two cycles were: (a) Increasing students' positive activity where in cycle I an average score of 46% was obtained, including the criteria for being quite active and in cycle II an average score of 85 was obtained. % includes very active criteria. From an average score of 46% in cycle I to 85% in cycle II. (b) Increased student learning outcomes after implementing the use of the chain whispering method where in cycle I the average score was 60.30 and in cycle II the average score was 95. Based on these results it can be concluded that the use of the chain whispering method was used. can improve the listening skills of class V SDI No. 147 Palalakkang, Galesong District, Takalar Regency.